IL-37 Exerts Anti-Inflammatory Effects in Fetal Membranes of Spontaneous Preterm Birth via the NF-κB and IL-6/STAT3 Signaling Pathway - Lulu Wang; Zheng Liu; Dongni Huang; Yuxin Ran; Hanwen Zhang; Jie He; Nanlin Yin; Hongbo Qi (Mediators of Inflammation)
Spontaneous preterm birth (sPTB), defined as delivery before 37 weeks of gestation, is thought to be a multifactorial syndrome. However, the inflammatory imbalance at the maternal-fetal interface promotes excessive secretion of inflammatory factors and induces apoptosis and degradation of the extracellular matrix (ECM), which can subsequently lead to preterm birth. As an anti-inflammatory molecule in the IL-1 family, interleukin-37 (IL-37) mainly plays an inhibiting role in a variety of inflammatory diseases. However, as a typical inflammatory disease, no previous studies have been carried out to explore the role of IL-37 in sPTB. In this study, a series of molecular biological experiments were performed in clinical samples and human amniotic epithelial cell line (Wistar Institute Susan Hayflick (WISH)) to investigate the deficiency role of IL-37 and the potential mechanism. Firstly, the results indicated that the expression of IL-37 in human peripheral plasma and fetal membranes was significantly decreased in the sPTB group. Afterward, it is proved that IL-37 could significantly suppress the production of tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6) in WISH cells. Simultaneously, once silence IL-37, LPS-induced apoptosis and activity of matrix metalloproteinases (MMPs) 2 and 9 were significantly increased. In addition, the western blot data showed that IL-37 performed its biological effects by inhibiting the NF-κB and IL-6/STAT3 pathway. In conclusion, our results suggest that IL-37 limits excessive inflammation and subsequently inhibits ECM remodeling and apoptosis through the NF-κB and IL-6/STAT3 signaling pathway in the fetal membranes.